Administración Zonal La Mariscal - Hajjar Ariss, Samir Nicolás (2017)
The thesis project is based on a rehabilitation of a very important area in the city of Quito. La Mariscal has always been known as an urban hypercenter which, over time, has lost its fundamental characteristics. Among them, the historicaly predominant residential use in the of the area has been diluted. That is why the workshop of 9th of the graduates of the 2017 University of the Americas proposes a “return to the center” as an urban plan, with a goal established until 2040. Individually the project discussed below, is based on a space where administrative civic tasks are combined with the public use of its inhabitants. The Administración Zonal La Mariscal, aims to be a project that facilitates the administrative processes that concern the inhabitants of the sector La Mariscal, while providing a comfortable space for all ages and demographic groups. It is also a point of intermodality of public transportation, with the aim of facilitate the comute of the inhabitants inside and outside the sector.